Sorbitol as a Cryptic Cause of Diarrhea - Anthony G. Catto-Smith; R. Brent Scott; Helen M. Machida; D. Grant Gall (Canadian Journal of Gastroenterology)
Sorbitol is a poorly absorbed monosaccharide widely used as a sweetener for dietetic foods and as a drug vehicle. Ingestion of sorbitol can lead to gastrointestinal complaints such as cramps and diarrhea. Two patients in whom unrecognized sorbitol ingestion produced symptoms which mimicked an exacerbation of another underlying disorder are presented. The diagnosis of sorbitol induced symptoms may be missed or delayed because patients do not appreciate that they are ingesting the compound in 'sugarless foods', and drug product information may not list its inclusion as a sweetener.